Islam and democracy - Saeed Khodaverdian (Kyklos, 2022)
The Muslim countries have a lower democracy level on average than the other countries. Yet, this cross-country comparison is not sufficient to blame Islam for the democracy deficit. This issue is related to the numerous fixed characteristics that differ across the countries and that also have an effect on democracy. When the differences are not considered, the estimates mix the effect of the fixed characteristics with the effect that Islam has on democracy. We show this issue for a large set of countries covering the period 1950–2015. In cross-country comparisons, we find a negative link between the share of Muslims in the total population and common measures for democracy. Yet, when the fixed characteristics are considered, the negative link vanishes. Thus, the lower democracy level has to be due to a fixed characteristic; it cannot be associated to (time-varying) Muslim shares. Numerous empirical specifications support this finding. We also measure Islam by the average per-day length of fasting during the month of Ramadan exploring whether the intensity of practicing the core teachings of Islam has a negative effect on democracy. Again, the evidence rejects a negative effect of Islam on democracy. If anything, the effect is positive. The findings are important for social coexistence.
Keywords: 300